The Cyanobacterial Photoactive Orange Carotenoid Protein Is an Excellent Singlet Oxygen Quencher . Issue 4 (18th April 2014) - Sedoud, Arezki; López-Igual, Rocío; ur Rehman, Ateeq; Wilson, Adjélé; Perreau, François; Boulay, Clémence; Vass, Imre; Krieger-Liszkay, Anja; Kirilovsky, Diana
Abstract : This work shows that the cyanobacterial photoactive orange carotenoid protein (OCP) protects Synechocystis cells from photoinhibition even under conditions in which it is unable to quench excess energy absorbed by phycobilisomes. OCP plays a dual role under light stress conditions, protecting cells against photooxidative stress by quenching excess energy and singlet oxygen. Abstract: Cyanobacteria have developed a photoprotective mechanism that decreases the energy arriving at the photosynthetic reaction centers under high-light conditions. The photoactive orange carotenoid protein (OCP) is essential in this mechanism as a light sensor and energy quencher. When OCP is photoactivated by strong blue-green light, it is able to dissipate excess energy as heat by interacting with phycobilisomes. As a consequence, charge separation and recombination leading to the formation of singlet oxygen diminishes. Here, we demonstrate that OCP has another essential role. We observed that OCP also protects Synechocystis cells from strong orange-red light, a condition in which OCP is not photoactivated. We first showed that this photoprotection is related to a decrease of singlet oxygen concentration due to OCP action. Then, we demonstrated that, in vitro, OCP is a very good singlet oxygen quencher. By contrast, another carotenoid protein having a high similarity with the N-terminal domain of OCP is not more efficient as a singlet oxygen quencher than a protein without carotenoid. Although OCP is a soluble protein, it is able to quench the singlet oxygen generated in the thylakoid membranes. Thus, OCP has dual and complementary photoprotective functions as an energy quencher and a singlet oxygen quencher.